Anti-adhesion properties of aminopropanol derivative with N-alkylaryl radical KVM-194 against Pseudomonas aeruginosa - HRYNCHUK, Nataliia; BUKHTIAROVA, Tetiana; DUDIKOVA, Daria; VRYNCHANU, Nina; NEDASHKIVSKA, Vira; BOIKO, Iryna; KOROTKYI, Yurii; BONDARENKO, Larisa (One Health & Risk Management, 2020)
Introduction. The present study assessed Pseudomonas aeruginosa surface characteristics, motility and adhesion properties under the influence of 1-[4-(1,1,3,3-tetra methyl butyl) phenoxy]-3-(N-benzyl hexa methylene iminium)-2-propanol chloride (KVM-194).Material and methods. The clinical strain P. aeruginosa 449 was used in the study. The cell surface hydrophobicity (CSH) was evaluated by adhesion to solvent (MATS test). Swimming, swarming and twitching motility of P. aeruginosa were studied by standard methods in media with different agar contents. Cells ability to adhere to polystyrene was assessed by the Christensen method. The effect of KVM-194, meropenem and ciprofloxacin on hydrophobicity and motility was evaluated both at 0.5 or 2.0 minimal inhibitory concentrations (MIC), while on adhesion abilities – only 0.5×MIC.Results. It was shown that 0.5× MIC KVM-194 reduced CSH of P. aeruginosa (by 16%, p˂0.05), affected swimming motility, and decreased its adhesion to polystyrene. The most pronounced changes in adhesion properties were recorded after 3-5 hours of pre-treatment with this compound. Moreover, it was proven that sub-MICs of meropenem and ciprofloxacin did not alter bacterial cells hydrophobicity and had no significant influence on P. aeruginosa motility and adhesion properties.Conclusions. The present study suggested that KVM-194 affected the initial steps of   P. aeruginosa biofilm formation and thus had tremendous potential for new antibiofilm agents’ development.